Implementasi Digital Marketing untuk Meningkatkan Omzet Industri Kecil Menengah (IKM) di Kabupaten Deli Serdang - Dharmawati; Nur Wulan; Sarudin; Ummul Khair; Suriati (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2026)
This community service program aimed to enhance the capacity of Small and Medium Industries (SMIs) in utilizing digital marketing as a marketing strategy in the digital era. The primary challenges faced by the partner organization included limited understanding of digital marketing, insufficient ability to identify target markets, and suboptimal utilization of digital platforms. The program was implemented through training, hands-on practice, and mentoring, covering the fundamentals of digital marketing, the identification of Unique Selling Propositions (USPs), the use of social media and online marketplaces, as well as the application of WhatsApp Business and paid advertising. The results demonstrated an improvement in participants' understanding of digital marketing strategies and their ability to create simple promotional content. Among the 25 participants, 2 (8%) were unable to develop digital marketing content, 4 (16%) had not yet completed the development of their business marketing content, whereas 19 (76%) successfully completed the creation of digital marketing content. This program is expected to encourage SMIs to sustainably increase their sales revenue and strengthen their competitiveness.